Cariprazine for acute and maintenance treatment of adults with schizophrenia: an evidence-based review and place in therapy - Citrome L (Dove Medical Press, 2018)
Leslie Citrome Department of Psychiatry and Behavioral Sciences, New York Medical College, Valhalla, NY, USA Abstract: Cariprazine is an oral antipsychotic approved in the US and EU for the treatment of schizophrenia. Cariprazine differs from other antipsychotics in that it is a dopamine D3- and D2-receptor partial agonist, with tenfold higher affinity for D3 receptors than for D2 receptors. Cariprazine is metabolized in two steps by CYP3A4 to didesmethyl-cariprazine (DDCAR). DDCAR has a long half-life of 1–3 weeks and is the predominant circulating active moiety. Efficacy and safety in persons with acute schizophrenia were assessed in four similarly designed, short-term, randomized, placebo-controlled clinical trials in nonelderly adults, with three studies considered positive and yielding a number needed to treat vs placebo for response (change from baseline ≥30% in Positive and Negative Syndrome Scale total score) of ten for the approved dose range of cariprazine 1.5–6 mg/day. The most common adverse reactions were extrapyramidal symptoms (15% and 19% for 1.5–3 and 4.5–6 mg/day, respectively, vs 8% for placebo) and akathisia (9% and 12.5% for 1.5–3 and 4.5–6 mg/day, respectively, vs 4% for placebo). For the approved dose range, rates of discontinuation because of an adverse event were lower overall for patients receiving cariprazine vs placebo (9% vs 12%). Weight and metabolic profile appear favorable. Cariprazine does not increase prolactin levels or prolong the electrocardiographic QT interval. Cariprazine has also been found to be effective for the maintenance treatment of schizophrenia by delaying time to relapse when compared with placebo (HR 0.45). A 26-week randomized clinical trial evidenced superiority of cariprazine over risperidone for the treatment of predominantly negative symptoms in patients with schizophrenia. Cariprazine is also approved in the US for the acute treatment of manic or mixed episodes associated with bipolar I disorder in adults and is being studied for the treatment of bipolar I depression and major depressive disorder. Keywords: cariprazine, didesmethyl-cariprazine, dopamine-receptor partial agonist, schizophrenia, dopamine D3 receptor